Cimandiri Watershed, Sukabumi District: A dynamic model for optimizing water resources - Yuswandi, Yuswandi; Priatna, Dolly; Rosadi, Rosadi (Indonesian Journal of Applied Environmental Studies, 2024)
Water is a very important element for human life. Humans cannot survive without water, therefore water is one of the basic needs for human survival. Water resources in Indonesia are abundant, but only a few can be utilized as drinking water. Of the total water available, only 5% is used for drinking water, while the rest is water that cannot be consumed before further treatment. In addition, the current trend is to reduce the supply of drinking water. In researching and evaluating the water resources of an area, the quantity and quality aspects must be considered because both factors are measures that need to be taken into account in the utilization of water resources. A water balance analysis is necessary to compare the water availability and demand in the Cimandiri Watershed in Sukabumi District. An overview of the state of the water balance in the Cimandiri Watershed in Sukabumi District is anticipated to be provided by this research. This study employs secondary data and is descriptive in nature, utilizing quantitative methods for data collection, processing, and analysis. This study approach comprises the following analyses: 2022–2052 surface water and groundwater sources; 2022–2052 population; industrial; tourism; agriculture and livestock water demand; as well as 2022–2052 water balance. The analysis of water availability and demand in 2052 showed that 263,639,967.40 m3 of water was available and 76,738,969.50 m3 of water was demanded. Thus, we must develop a strategy and take action to ensure that extra water is used effectively and responsibly, thereby establishing a buffer for future shortages while also benefiting the environment and the community.